11 Aspirations to focus on new MOHE direction to boost national higher education - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PUTRAJAYA, 30 January 2023 - Minister of Higher Education, Yang Berhormat Dato’ Seri Mohamed Khaled Nordin has initiated 11 aspirations that would be a milestone in efforts and guidance to boost the Malaysian education sector to be more quality and recognised.